Manajemen Pondok Pesantren Dalam Meningkatkan Kedisiplinan Santri: (Multikasus di Pondok Pesantren Darullughah Wadda’wah Bangil Kabupaten Pasuruan & Pondok Pesantren Darussalam Takhassus Martapura Kabupaten Banjar) - Ubaidillah, Muhammad; M. Ulyan (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2023)
This study aims to reveal the Management of Islamic Boarding Schools in Improving Santri Discipline at Darullughah Wadda'wah Islamic Boarding Schools and Madrasah Takhassus Darussalam which will focus on improving discipline. The research method used in this study is a type of qualitative research. The research approach in this study is descriptive. Based on the results of the research: (1) Planning for discipline education for students plans rules that must be applied, then conveys them to all students to follow and obey. If it is not followed according to the rules, students who violate these rules will get sanctions / punishments appropriately, to make students who are highly disciplined and responsible for what they do. and for supporting the discipline of these students we have very adequate facilities/means. (2) Discipline management has complied with the regulations set. Management is carried out by compiling an educational calendar and adjusted annually by the school to regulate learning activities. Study time arrangements refer to content standards and are adjusted to the calendar of the Darullughah Wadda'wah Islamic Boarding School and Takhassus Darussalam Madrasah, regional needs, the needs of students and the community, as well as provisions from the government. (3) While the obstacles are Obstacles in the management of discipline, of course there are students who violate the rules in the implementation of discipline. Thus, the solution must be followed up starting from compiling data, planning, organizing, implementing, up to monitoring and evaluation. then management produces something that can be a source of refinement and improvement in the management of santri discipline.